2019
DOI: 10.1029/2018gc007931
|View full text |Cite
|
Sign up to set email alerts
|

Microstructures, Water Contents, and Seismic Properties of the Mantle Lithosphere Beneath the Northern Limit of the Hangay Dome, Mongolia

Abstract: To constrain the deformation, thermal evolution, and seismic properties of the mantle lithosphere beneath the Hangay Dome, we have analyzed the microstructures, crystal preferred orientations (CPO), and hydrogen concentrations of olivine and pyroxenes of 50 mantle xenoliths carried up by Cenozoic basalts from Zala, Haer, and Shavaryn‐Tsaram from Tariat, Mongolia. Most xenoliths are medium‐ to coarse‐grained spinel‐lherzolites, but four contain garnet + spinel. Coarse granular, highly annealed microstructures p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 100 publications
(187 reference statements)
0
15
0
Order By: Relevance
“…The recrystallized fraction is quantified by the area fraction composed by grains with low intragranular misorientation (grain orientation spread, GOS < 1.5°). Dashed line in (b) indicates the shape factor of a well‐equilibrated synthetic olivine aggregate composed by polygonal crystals (Demouchy et al, 2019). Data presented in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…The recrystallized fraction is quantified by the area fraction composed by grains with low intragranular misorientation (grain orientation spread, GOS < 1.5°). Dashed line in (b) indicates the shape factor of a well‐equilibrated synthetic olivine aggregate composed by polygonal crystals (Demouchy et al, 2019). Data presented in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…The recrystallized fraction is quantified by the area fraction composed by grains with low intragranular misorientation (grain orientation spread, GOS < 1.5°). Dashed line in (b) indicates the shape factor of a well-equilibrated synthetic olivine aggregate composed by polygonal crystals (Demouchy et al, 2019). Data presented in Table 2.…”
Section: Microstructuresmentioning
confidence: 99%
“…(2) dislocation-assisted grain boundary sliding as proposed by Hirth and Kohlstedt (1995) (see also Hansen et al, 2011Hansen et al, , 2012, which is then grain size dependent; (3) diffusionaccommodated grain boundary sliding (Miyazaki et al, 2013), which is limited to nanoscale grains of olivine (± pyroxenes) and thus is unlikely to be efficient in mantle olivinerich rocks with grain sizes of 0.1-10 mm and under high lithostatic pressure (> 1 GPa); (4) elastically accommodated grain boundary sliding (Jackson et al, 2013), which also requires very fine grained polycrystalline olivine of constant grain size, in which the grain boundary network is considered equivalent to a very low viscosity layer; however, this contradicts the crystalline sintering observed at high pressure and temperature (Hiraga et al, 2004;Burnard et al, 2015); (5) ionic diffusion operating only at grain boundaries as proposed by Detrez et al (2015), but they also showed that this mechanism cannot sustain a non-linear rheology in an anisotropic solid such as olivine; (6) disclination-assisted dislocation creep proposed by Cordier et al (2014), which involves rotational defects located near grain boundaries (see Sect. 7); or (7) the potential existence of disconnections located at grain boundaries such as the one observed in aluminum metal (see Sect.…”
Section: Olivine Paradoxmentioning
confidence: 98%